Effects of conditioning of sepiolite prior to cobalt and nickel removal - Kocaoba, Sevgi; AKYÜZ, ZEKİ TANIL (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2005)
The effects of treatment and conditioning on sepiolite for the removal of Co2+ and Ni2+ from aqueous solutions were investigated by using a batch-type method. Effects of factors such as pH, concentration, stirring time, stirring speed and sorbent amount on adsorption were investigated. The initial and final concentrations of heavy metals were determined by means of atomic absorption spectrophotometer. Sorption data were interpreted in terms of Langmuir equations. The results provide support for the adsorption of these metals onto sepiolite. As a result, the sepiolite studied may be used for removal of Co2+ and Ni2+ from aqueous solutions.
Keywords: cobalt; nickel; sepiolite; removal; activated carbon; heavy-metals; aqueous-solutions; ion-exchange; sodium-salts; waste-water; adsorption; separation; lead; CO(II)/NI(II); kobalt; nikel; sepiyolit; uzaklaştırma; aktif karbon; ağır metaller; Sulu-çözümler; iyon değişimi; atık su; ayrılık; kurşun